246 MODIFICATIONS OF TYROSINE AS BIOMARKERS OF ATHEROSCLEROSIS IN SYSTEMIC LUPUS ERYTHEMATOSUS. (1st January 2006) - Caldwell, R. D.; Fleury, T. W.; Salmon, J. E.; Roman, M. J.; Oates, J. C.
Abstract : Background: Systemic lupus erythematosus (SLE) is an independent risk factor for coronary artery disease. Age, antiphospholipid antibody status, duration of disease, and the SLE damage index associate with atherosclerosis in SLE patients. 3-Chlorotyrosine (3CT) and 3-nitrotyrosine (3NT) are surrogate markers of hypochlorous acid and peroxynitrite production, and their levels correlate with cardiovascular disease in the general population. Orthotyrosine (OTyr) and metatyrosine (MTyr) are surrogate markers of hydroxy radicals that are seen in states of oxidative stress such as diabetic vascular disease. Furthermore, serum 3NT and markers of oxidant stress are elevated in patients who have circulating antiphospholipid antibodies. 3NT levels are also elevated in active SLE and lupus renal disease. We feel that measuring serum protein tyrosine modifications is a rational approach to predict atherosclerotic disease in the setting of SLE because these markers reflect mechanisms of disease in both disorders. Methods: 197 SLE patients were recruited as part of a longitudinal study of atherosclerosis in lupus described by Roman et al in 2003. Carotid ultrasound (US) measurements were performed at entry and at 2 years. Common, internal, and external carotid arteries were examined in M mode for plaque, and both common carotid arteries were examined for intima media thickness (L/R IMT). Blood was collected for serum at entry. 183 of these serum samples were precipitated with ethanol, digested with pronase, and filtered. The tyrosine modifications were quantitated using high-performance liquid chromatography with electrochemical detection (HPLC-ED). The results were reported as ratios of 3CT, 3NT, OTyr, and MTyr to tyrosine (Tyr). Results: Linear regression analysis using age, race, 3CT, 3NT, OTyr, and MTyr as input variables and IMT thickness and plaque as output variables demonstrated age was a significant predictor of all surrogate markers of atherosclerosis (p < .05). L IMT correlated with OTyr (p = .02) and age (p < .001). R IMT correlated with age. Discussion: The correlation of left carotid IMT with OTyr is consistent with the recognized role of oxidative stress in atherosclerosis. Serum 3CT, 3NT, OTyr, and MTyr levels measured at time zero are not predictive of atherosclerosis as measured by plaque on carotid US. This may reflect variability of these measures with lupus disease activity. A sensitive measure of changes in lupus disease activity should be included as a covariable in future studies.